Modular Inspection Equipment Design for Modular Structured Mechatronic Products – Model Based Systems Engineering Approach for an Integrative Product and Production System Development. (2016) - Lukei, Meinolf; Hassan, Bassem; Dumitrescu, Roman; Sigges, Thorsten; Derksen, Viktor
Abstract: Quality control is an essential part of the production of modular mechatronic systems. Especially the quality inspection of the overall system at the end of the production is of extraordinary importance. The associated inspection equipment can also be a mechatronic system, which is often explicitly designed and manufactured for one product with a large expenditure of time. In order to have the needed inspection equipment ready by the start of production (SoP) and to consider additional requirements to the product, which are produced by the inspection equipment concept, an integrative mechatronic product and inspection equipment development procedure is needed. Furthermore, the inspection system has to consider the modularity of the system and often has to be designed in a modular way. Nowadays, the development of complex mechatronic systems is often carried out with the help of model-based systems engineering (MBSE) methods. Consequently, the inspection equipment should also be designed with the help of MBSE. This paper describes an integrative product and inspection equipment procedure for modular mechatronic systems with the help of MBSE. Especially the peculiarity of the modularity is described and validated with the help of an application example.